Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69645
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Multipoint Optimization of a Transonic Turbocharger Compressor

Abstract: A transonic centrifugal compressor for turbocharger applications has been redesigned by means of a multidisciplinary multipoint optimization system composed of: a 3D Navier-Stokes solver, a Finite Element stress Analyzer, a Genetic Algorithm and an Artificial Neural Network. The latter makes use of a database, containing the geometry and corresponding performance of previously analyzed impellers and allows a considerable reduction in computational effort. The performance of every new geometry is verified by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The Mach number distributions on the blade surface and passage could aid in understanding how the efficiency of the compressor increased owing to optimization of the beta distribution. The lower suction side Mach number distribution at the shroud leads to a reduction in shock losses, and shock boundary layer interaction losses in the blade passage therefore improved efficiency, as expected [16]. In this study, remarkable changes were observed in the shroud rather than in the hub.…”
Section: Comparison Of the Baseline (Base Main-base Splitter) And Optmentioning
confidence: 51%
See 3 more Smart Citations
“…The Mach number distributions on the blade surface and passage could aid in understanding how the efficiency of the compressor increased owing to optimization of the beta distribution. The lower suction side Mach number distribution at the shroud leads to a reduction in shock losses, and shock boundary layer interaction losses in the blade passage therefore improved efficiency, as expected [16]. In this study, remarkable changes were observed in the shroud rather than in the hub.…”
Section: Comparison Of the Baseline (Base Main-base Splitter) And Optmentioning
confidence: 51%
“…In the standard geometry definition of the radial impeller, the parameterized hub and shroud curves coupled with beta distribution, which is the angle between the meridional plane (m) and blade camber line (s) (Figure 1), are generally considered [16]. In this study, in particular, the beta distribution itself on the main blade is parameterized and investigated with additional parameters of the splitter leading edge to optimize the compressor aerodynamically.…”
Section: Geometry Parameterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential evolution algorithm and the artificial neural network (ANN) were used to improve the efficiency and reduce the impeller inertia while limiting the stress to an allowable level at reasonable computational cost. Van den Braembussche et al [11] conducted a multidisciplinary multipoint optimization for a transonic turbocharge compressor. The operating range is guaranteed by a two-step optimization procedure.…”
Section: Introductionmentioning
confidence: 99%